Pengimplementasian Model Pembelajaran Kooperatif Tipe Talking Stick untuk Meningkatkan Hasil Belajar PKn Siswa Kelas IV di SDN 3 Dangintukadaya - Wahyuni, Luh Putu Eka Sri; Sudewiputri, Made Padmarani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Citizenship Education is one of the important indicators in an education. To form the character and moral values of a student, it is necessary to have character education, all of which are summarized in Civics learning. Therefore, Civics subjects are very important given to students. To achieve the learning objectives there are many influencing factors including the teacher factor. In teaching the teacher of course already has a design in achieving learning goals such as using interesting learning models and the latest learning media. The learning process in Civics subjects is also still widely carried out withconventional models or methods so that the impact on learning activities is still low which can then affect students' interest in learning Civics. The purpose of this research is to determine the improvement of student learning outcomes in Civics Class IV subjects at SDN 3 Dangintukadaya after the Talking Stick Type Cooperative learning model is applied. The method he uses is class action which consists of 4 stages, namely: 1) action plan, 2) action implementation, 3) action observation and evaluation, and 4) reflection. Class action is applied to the fourth grade students, totaling 33 people at SD Negeri 3Dangintukadaya. The data analysis technique is descriptive statistical analysis method. From theresults of data analysis there was an increase in the average value of student learning outcomes from cycle I to cycle II by 9.00%, while from the initial reflection to cycle II it was 21.60%. With theapplication of learning like this, it can improve the learning outcomes of fourth grade students at SDNegeri 3 Dangintukadaya.